Atropine 0.01% for the Control of Myopia in Chinese Children: Effect on Accommodation Functions and Pupil Size - Yuliang Wang; Jing Yao; Xiaomei Qu (Journal of Ophthalmology)
Background. To explore the effect of atropine 0.01% on accommodation functions and pupil size for safely and effectively controlling myopia in Chinese children. Methods. This was a single-center randomized clinical trial. 63 participants with myopia of at least −0.50 D and astigmatism of ≤−2.50 D were enrolled and randomized to receive atropine 0.01% once nightly with regular single-vision lenses or to wear regular single-vision lenses, in an allocation ratio of 3 : 2. Primary outcomes included changes of accommodation functions, pupil diameter, distant and near best-corrected visual acuity (BCVA), near stereoacuity, and intraocular pressure (IOP). Secondary outcome was myopic progression at 6 months. Results. 61 participants completed the follow-up. Compared with the control group, the atropine-treated children showed a statistically significant increase in pupil diameter after 6 months (0.7 ± 0.7 vs. 0.1 ± 0.5 mm, P=0.01). Despite the enlarged pupil, routine vision-related activities were not affected. The mean changes in accommodative functions, BCVA, near stereoacuity, and IOP, did not differ significantly between the groups. At 6 months, participants in the control group showed greater myopia progression than those in the atropine group (spherical equivalent: −0.60 ± 0.43 vs.−0.30 ± 0.42 D, P<0.001; axial length: 0.35 ± 0.20 vs. 0.24 ± 0.16 mm, P=0.001). Conclusions. Atropine 0.01% eye drops significantly increased pupil diameter less than one mm, but it did not affect accommodative functions, BCVA, near stereoacuity, and IOP. Combined with its reducing myopia progression, atropine 0.01% can be used as a safe and effective treatment for myopia in Chinese children.